Syngué sabour et Maudit soit Dostoïevski d’Atiq Rahimi : le féminin et le masculin dans le monde intégriste - Zdrada-Cok, Magdalena (Romanica Silesiana)
Syngué sabour and Maudit soit Dostoïevski by Atiq Rahimi : the Feminine and the Masculine in the Fundamentalist World The article aims at the analysis of Syngué sabour and Maudit soit Dostoïevski by Atiq Rahimi. The study is concentrated on the ideological construction of femininity and masculinity in the world dominated by fundamentalism and war (Afghanistan civil war in the 90s). The article researches some intertextual relations (between Rahimi and Dostoïevski) and the narrative strategies which represent the relationship between the individual and the political power. Key words: civil war in Afghanistan, fundamentalism, femininity and masculinity, narrative strategies, intertextual relations.